Tafsir Maqāṣidi dan Pengembangan Kisah Al-Qur’an: Studi Kisah Nabi Bermuka Masam dalam QS. Abasa [80]: 1-11 - Althaf Husein Muzakky (Qur'an and Hadith Academic Society, 2021)
The opinion that the maqāṣidi interpretation is only intended for paragraphs of law should not be correct. The method of maqāafsidi interpretation can also be applied to the verse of the story for the side of 'ibrah (lesson) contained in the al-Qur'an. So far the study of the story of the Koran has not discussed much of the verse „itāb rebukes‟ relation to the Prophet's kema‟ṣūman. This paper is here to answer the question of how to interpret the story of the Qur'an using the maqāṣidi interpretation in the QS. 'Abasa, and why the maqāṣid behind the story is important to be discussed in the study of' ulūm al-Qur'an. This study is classified as a literature study (library research), with the maqāṣidi method of interpretation proposed by Abdul Mustaqim and the method of the verse of the story 'Abd al-Karīm al-Khaṭīb, it is found that the application of the maqāṣidi interpretation of the verse of the story of the story has a deep distinction in developing' ibrah (story have maqāṣid ẓāhir and bātin so that studies can be developed through maqāṣid al-syari'ah and maqāsid new fundamental values.